Alerting attention is sufficient to induce a phase-dependent behavior that can be predicted by frontal EEG - Mentzelopoulos, Georgios; Driscoll, Nicolette; Shankar, Sneha; Kim, Brian; Rich, Ryan; Fernandez-Nunez, Guadalupe; Stoll, Harrison; Erickson, Brian; Medaglia, John Dominic; Vitale, Flavia (Frontiers in Behavioral Neuroscience, 2023)
Recent studies suggest that attention is rhythmic. Whether that rhythmicity can be explained by the phase of ongoing neural oscillations, however, is still debated. We contemplate that a step towards untangling the relationship between attention and phase stems from employing simple behavioral tasks that isolate attention from other cognitive functions (perception/decision- making) and by localized monitoring of neural activity with high spatiotemporal resolution over the brain regions associated with the attentional network. In this study, we investigated whether the phase of electroencephalography (EEG) oscillations predicts alerting attention. We isolated the alerting mechanism of attention using the Psychomotor Vigilance Task, which does not involve a perceptual component, and collected high resolution EEG using novel high-density dry EEG arrays at the frontal region of the scalp. We identified that alerting attention alone is sufficient to induce a phase-dependent modulation of behavior at EEG frequencies of 3, 6, and 8 Hz throughout the frontal region, and we quantified the phase that predicts the high and low attention states in our cohort. Our findings disambiguate the relationship between EEG phase and alerting attention.